2023
DOI: 10.1186/s40359-023-01311-2
|View full text |Cite
|
Sign up to set email alerts
|

How social media usage affects psychological and subjective well-being: testing a moderated mediation model

Chang’an Zhang,
Lingjie Tang,
Zhifang Liu

Abstract: Background A growing body of literature demonstrates that social media usage has witnessed a rapid increase in higher education and is almost ubiquitous among young people. The underlying mechanisms as to how social media usage by university students affects their well-being are unclear. Moreover, current research has produced conflicting evidence concerning the potential effects of social media on individuals' overall well-being with some reporting negative outcomes while others revealing bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…However, network usage may also cause some negative effects. For example, addiction to the Internet, social media anxiety and other issues ( Wu, 2023 ; Zhang et al, 2023 ), which may have a negative impact on subjective well-being. Therefore, it is necessary to pay attention to the reasonable guidance and management of network use.…”
Section: Discussionmentioning
confidence: 99%
“…However, network usage may also cause some negative effects. For example, addiction to the Internet, social media anxiety and other issues ( Wu, 2023 ; Zhang et al, 2023 ), which may have a negative impact on subjective well-being. Therefore, it is necessary to pay attention to the reasonable guidance and management of network use.…”
Section: Discussionmentioning
confidence: 99%
“…We controlled for participants’ gender, age, tenure and education level, all of which have been found to influence employees’ behavior [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the findings of Lamash (2023), there is a significant correlation between well-being and social interaction skills and social media use. This is reinforced by research by Zhang et al, (2023), which states that social media has a positive effect on psychological well-being (PWB) and subjective happiness (subjective well-being). Chai et al (2019) suggested that the use of social networking sites (SNS) has a positive direct effect on adolescents' subjective well-being.…”
Section: Definition Of Social Media Usagementioning
confidence: 96%
“…This scoping review included ten articles, all of which were empirical studies. This research was conducted in different countries, namely Taiwan (Hsu et al, 2020); (Lai et al, 2018), Turkey (Koç & Turan, 2020), USA and Canada (Wirtz et al, 2020), China (Chai et al, 2019;Zhang et al, 2023), Kazakhstan (Mahmood et al, 2023), Australia (Jarman et al, 2021), Croatia (Keresteš & Štulhofer., 2019), Netherlands (Du et al, 2021). The subjects of these studies were adolescents with the status of high school and university students.…”
Section: Study Characteristicsmentioning
confidence: 99%